Analysis of Poland’s social control system in 1989-2019 - Paweł Kawalerski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2022)
The whole paper is based on the terminological convention of the theory of autonomous systems and information logic along with derivative concepts, derived according to certain rules of defining the theory. Indicated approach allowed to explicate first causes (sufficient and necessary) of social system security. In turn, the use of selected noneractive methods – mainly the analysis of statistical data, provided an evaluation of the dynamics of changes in the power supply track of Poland with the inclusion of structural cause (sociomass) and causal cause (socioenergy) in the indicated time period (from 1989 to 2019), which can be classified as social action from the strategic level. The main conclusions are: the Polish social system is characteristic of the functioning of a dynamic regressive system of social control. The organizers of Poland’s social system aim at blocking intensive development and apply methods characteristic for an extensive system of social control.